Social Campaign Design Through ZIS Digital Visual Communication Media For BAZNAS Institutions In South Sumatera Province - Ramadoni, Muhamad Afdoli; Kurnia, Eva (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research is motivated by problems related to low awareness of the importance of ZIS (Zakat, Infak, Sedekah) in the community, therefore the authors designed a social-themed campaign program Baznas On The Road For Savings which is expected to be helpful for the public as a means of helping South Sumatera BAZNAS programs to provide awareness about ZIS awareness both digitally and offline in the Digital Age. The method used is qualitative, with BAZNAS staff of South Sumatera and the community participating in the social campaign program as informants. This research focuses on designing social campaigns to increase ZIS awareness through social visual media communication. As for the deficiency and success factors, it was found that the deficiencies were due to human weakness and lack of awareness to carry out ZIS, systems that still needed to run optimally, HR factors, and Muzakki's trust. In contrast, the supporting factors were supported by application features and social campaigns to increase ZIS awareness in the community. Through the design of the BAZNAS On The Road For Savings campaign, it is hoped that it can increase awareness of ZIS (Zakat, Infak, Sedekah) in the community, so that the success of the campaign can be properly controlled in subsequent developments.